Context-aware mobile and ubiquitous computing for enhanced usability adaptive technologies and applications - Stojanović, Dragan (Premier reference source, 2009)
"This book covers advanced aspects of context-awareness and up-to-date topics in context management, development and adaptation of context-aware applications and service, context-aware security and access control, incorporating context-awareness in service-oriented architectures" - Provided by publisher